Engineering mechanics statics - Bedford, Anthony; Fowler, Wallace; Schiavone, Peter (Prentice Hall, 2008)
This supplement is divided two parts. Part I is a workbook which explains how to draw and use free-body diagrams when solving problems in statics. Part II provides a section-by-section, chapter-by-chapter summary of the key concepts, principles, and equation from A.Bedford & W.Fowlers text.